THE EFFECT OF PRIMARY AGING PROCESS OF GAMMA PRIME CHANGES IN THE MICROSTRUCTURE OF AIRCRAFT TURBINE BLADE RENE 142 MATERIAL - Agung Satria, Dwi
The turbine blade is an important component of a plane’s engine. One of the materials used on this component is Rene 142 which is made from nickel-base superalloy. The microstructure is an important factor that influences the properties of this material through gamma prime (?’) and gamma (?). Gamma prime is divided into primary ?’ and secondary ?’. Previously, microstructure modification had been carried out through a solution treatment process at a temperature of 1250°C for 30 and 60 minutes which was then cooled in the air (air cooling) and the furnace (furnace cooling). However, the resulting shape is still spherical, semi spherical, and irregular. So, a primary aging process is needed to change the primary ?’ to cuboid. In this study, the primary aging process was carried out for the material produced from the entire solution treatment process. This process is carried out at a temperature of 1121°C for 30 minutes and cooled in the air. The microstructure after this process was viewed using the FESEM tool. As a result of this process, the primary ?’ form becomes a cuboid. This change was also followed by an increase channel gap of the primary ?’. After that, the result of solution treatment with cooling in the air has an increase in area fraction, width, and length. Then, the results of solution treatment with cooling in the furnace had a decrease in area fraction. However, it didn’t change the width and length of the primary ?’.